Dose water extract of cinnamon (cinnamomum zeylanicum) exhibits anti-diabetic properties in cultured 3T3-L1 adipocytes: a concurrent assessment of adipogenesis, lipolysis and glucose uptakes - Azahari, Nuraniza; Khattak, Muhammad Muzaffar Ali Khan; Bakhtiar, M. Taher; Arief Ichwan, Solachuddin Jauhari (Science and Education Publishing, 2014)
Cinnamon is a common spice which is widely advocated for its efficacy controlling of hyperglycemia. However, the mechanism of action has yet to be established for the effect on the blood glucose concentration. Cinnamon was extracted with water and induced to cell line namely 3T3-L1 preadipocyte (American Type cell Culture Collection). The cell proliferation, differentiation (adipogenesis) and glucose uptake activity were assessed by measuring the uptake of radio-labelled glucose. Furthermore, for comparison glucose oxidase assay was also performed by using Glucose Assay Kit (Sigma-Aldrich, Inc). The collected data was statistically analysed using SPSS version 12.0 for any possible differences. This study revealed that there was a significant (P<0.01) increase the activity/adipogenesis. This increase activity was accompanied by significant (P<0.01) increase in the glucose uptake and reduced catalytic activity of lipids (lipolysis). The finding reveals that C. Zeylanicum extract has similar effect to that of insulin activity. The present study suggests that the cinnamon enhances glucose uptakes, reduces the lipid breakdown and resembles insulin activity.